1997
DOI: 10.1002/(sici)1097-0215(19970703)72:1<149::aid-ijc21>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 functions as an autocrine growth factor in human bladder carcinoma cell linesin vitro

Abstract: Interleukin (IL)-6 is reported to function as a growth factor for renal and prostatic carcinomas. We conducted the present study to define the role of IL-6 in the growth of normal and neoplastic urothelial cells. Human bladder carcinoma cell lines (253J, RT4 and T24) and primary cultured human urothelial cells derived from normal ureters were used. Recombinant human IL-6 stimulated the growth of bladder carcinoma cell lines far better than that of normal urothelial cells (p F 0.001). All carcinoma cell lines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
258
2
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(274 citation statements)
references
References 15 publications
12
258
2
2
Order By: Relevance
“…Furthermore, criss-cross experiments showed that supernatants of the autologous cell line of bladder cancer not only stimulated the proliferation of its own cells, but also the growth of other bladder cancer cell lines, which suggested the production of common autocrine growth factors for bladder cancer cells [28]. Some factors or their receptors involved in autocrine loop mechanism of bladder cancer cells have been confirmed, such as IL-6, EGFR, IFN-β, transferrins-like substance etc [34], [35]. But more other unknown factors which may play key roles in autocrine mechanisms of TCCs need to be further characterized.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, criss-cross experiments showed that supernatants of the autologous cell line of bladder cancer not only stimulated the proliferation of its own cells, but also the growth of other bladder cancer cell lines, which suggested the production of common autocrine growth factors for bladder cancer cells [28]. Some factors or their receptors involved in autocrine loop mechanism of bladder cancer cells have been confirmed, such as IL-6, EGFR, IFN-β, transferrins-like substance etc [34], [35]. But more other unknown factors which may play key roles in autocrine mechanisms of TCCs need to be further characterized.…”
Section: Discussionmentioning
confidence: 94%
“…Literature reports about either growth-promoting or -inhibiting activities of IL-6 in androgen-sensitive LNCaP cells are available (Okamoto et al, 1997;Lou et al, 2000;Lin et al, 2001). In our previous studies, proliferation of LNCaP cells was consistently decreased after exposure to IL-6, whereas LNCaP-IL-6 þ cells were not affected by the exogenous cytokine .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that as part of the systemic inflammatory response to the tumour there is a release of proinflammatory cytokines and growth factors, which not only stimulate tumour growth (Abramovitch et al, 1999;Coussens and Werb, 2002) but also produce profound catabolic effects on host metabolism (Kotler, 2000). For example, interleukin-6, produced by the tumour or infiltrating inflammatory cells, is recognised as a growth promoter in bladder cancer (Okamoto et al, 1997;Andrews et al, 2002). Interleukin-6 also stimulates liver production of acute-phase proteins, such as Creactive protein, which increases the demand for certain amino acids, which, if limited in the diet, must be obtained from the breakdown of skeletal muscle Preston et al, 1998).…”
Section: Discussionmentioning
confidence: 99%